Internship as a category of labor law - Andriiv, Vasyl; Vakhonieva, Tetiana (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article is devoted to the study of the peculiarities of the legal regulation of the internship within the framework of labor relations. The main types, signs and consequences of the internship are determined. Certain problems of legal regulation of internships in labor law are revealed.